2000
DOI: 10.1177/107179190000700102
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Education in Colleges: Toward a 21st Century Paradigm

Abstract: Executive SummaryThe industrial view of leadership is inadequate for educational purposes because it does not address the nature of the complex social relationships among people who practice leadership, nor does it accurately accommodate their purposes, motives, and intentions. A distinction among the practices of training, development, and education provides a means to explore an understanding of these complex social relationships relative to the preparation of leaders for the future. The content of leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 4 publications
0
86
0
5
Order By: Relevance
“…Contemporary student leadership development theories (e.g., Kouzes and Posner 2002;Rost and Barker 2000;Shek et al 2018) conceptualized leadership in relation to the contribution to the common good, and uphold the cultivation of capacities that enable one to transcend beyond the self in a leadership process, including moral values such as integrity, other-oriented qualities such as caring toward others, and a service mindset. The course "Service Leadership" demonstrated that the knowledge about and positive attitudes toward these leadership ideologies are educable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary student leadership development theories (e.g., Kouzes and Posner 2002;Rost and Barker 2000;Shek et al 2018) conceptualized leadership in relation to the contribution to the common good, and uphold the cultivation of capacities that enable one to transcend beyond the self in a leadership process, including moral values such as integrity, other-oriented qualities such as caring toward others, and a service mindset. The course "Service Leadership" demonstrated that the knowledge about and positive attitudes toward these leadership ideologies are educable.…”
Section: Discussionmentioning
confidence: 99%
“…According to the contemporary leadership development models, leadership programs have shifted their focus on building up management skills to that on cultivating collaboration qualities, caring disposition, moral values, and other capacities that facilitate the attainment of common good (Rost and Barker 2000). Leadership programs are usually intentionally designed and offered to students to provide them with opportunities to learn knowledge, skills, values and beliefs related to leadership (Haber 2006).…”
Section: Leadership Programs In Higher Educationmentioning
confidence: 99%
“…Critical leadership theorists point out that this understanding of leadership cannot be distinguished from, but equals management (e.g. Rost, 1991). In the vertical context of a network organization and a stakeholder environment, however, the task of leadership gets a new meaning.…”
Section: Who Are the Actors In The Leader-follower Relationship?mentioning
confidence: 99%
“…If leadership resides within such relationships (Foster, 1989;Rost, 1991) and if the purpose of leadership is to achieve a commonly desired vision, then the primary focus of the leader needs to be on the relationships with those who have a stake in the leadership project. The leader becomes a cultivator of these relationships in terms of their quality and desired values base and a facilitator of relational processes (we will specify further below what that means for a leader's roles).…”
Section: Who Are the Actors In The Leader-follower Relationship?mentioning
confidence: 99%
“…71 Joseph C. Rost es autor de la obra Liderazgo para el Siglo XXI (1991), donde se plantea los retos de la práctica del liderazgo en el contexto global del siglo XXI. Además ha desarrollado su carrera investigadora en la University of San Diego, reflexionando sobre diversas cuestiones relacionadas con el liderazgo y la ética (Rost 1993(Rost , 1995(Rost , 1997Rost y Barker 2000).…”
Section: Liderazgo Vs Managementunclassified